Cushing Syndrome: The Role of MSCs in Wound Healing, Immunosuppression, Comorbidities, and Antioxidant Imbalance - Caffarini, Miriam; Armeni, Tatiana; Pellegrino, Pamela; Cianfruglia, Laura; Martino, Marianna; Offidani, Annamaria; Di Benedetto, Giovanni; Arnaldi, Giorgio; Campanati, Anna; Orciani, Monia (Frontiers in Cell and Developmental Biology, 2019)
Cushing Syndrome (CS), caused by glucocorticoid (GCs) excess, is strictly connected to onset of different metabolic diseases and impaired wound healing. The source of excessively high levels of GCs allows the identification of endogenous and exogenous (iatrogenic) CS. Iatrogenic patients usually receive also anti-metabolites serving as the foundation to modern steroid-sparing immunosuppressive therapy. Tissues mainly targeted by CS are bone and fat, both derived from progenitor cells named Mesenchymal Stem Cells (MSCs). In addition, the pathogenic role of MSCs in other diseases sharing common properties with CS, such as an altered inflammatory profile and increased oxidative stress, has been identified. In this light, MSCs isolated from skin of control healthy subjects (C-MSCs), patients affected by endogenous CS (ENDO-MSCs), patients affected by iatrogenic CS (IATRO-MSCs) and patients affected by exogenous CS receiving steroid-sparing drugs (SS-MSCs), respectively, have been isolated and analyzed. ENDO- and IATRO-MSCs showed a reduced differentiative potential towards osteogenic and adipogenic lineages compared to C-MSCs, whereas SS-MSCs re-acquired the ability to differentiate, with a trend similar to control cells. In addition, MSCs from CS groups, compared to control MSCs, displayed a reduction in the secretion of cytokines (immune-suppression), a decreased expression of genes related to wound healing and a dysregulation of the enzymes/genes related to antioxidant capacity. In conclusion, our results suggest that the hallmarks of CS, such as wound healing impairment and immunosuppression, are already detectable in undifferentiated cells, which could be considered a potential therapeutic early target for control of CS.